Siddha Herbal Formulations in Dental Care: A Comprehensive Review of Traditional Remedies - Ramasamy, Suresh; Pazhani, Shanmugapriyan; Balasubramani, Abarna; Radhakrishnan, Shanmu; Mani, Karthic Vedhachalam (Asian Journal of Biological and Life Sciences)
Oral health is a critical component of overall well-being, yet dental diseases remain widespread due to factors like poor hygiene and limited awareness. Traditional systems like Siddha medicine offer valuable insights into natural, cost-effective oral care solutions. This review explores 43 Siddha herbal formulations used in dental care, focusing on their traditional applications and potential therapeutic benefits. Plant parts such as bark, roots, leaves, seeds, and latex are used in diverse forms-decoctions, powders, fumes, chews, and oil preparations-to treat conditions like gingivitis, toothache, oral ulcers, and periodontitis. Classical Siddha texts and contemporary research validate the antimicrobial, anti-inflammatory, analgesic, and astringent properties of these herbs. The study highlights the relevance of integrating Siddha formulations into modern dental practice, especially for underserved populations. However, further pharmacological validation, standardization, and clinical trials are essential to ensure safety and efficacy. This synthesis encourages a holistic approach to oral healthcare by bridging traditional knowledge and contemporary science.
Keywords: Gingivitis treatment; Herbal dental formulations; Medicinal plants; Oral health; Siddha medicine; Traditional remedies